Prediction of the Omp16 Epitopes for the Development of an Epitope-based Vaccine Against Brucellosis - Rezaei, Marzieh; Rabbani-khorasgani, Mohammad; Zarkesh-Esfahani, Sayyed H.; Emamzadeh, Rahman; Abtahi, Hamid (Infectious Disorders - Drug Targets, 2019)
Background: Brucellosis is an infectious disease caused by Brucella bacteria that cause disease in animals and humans. Brucellosis is one of the most common zoonotic diseases transmitted from animals-to-human through direct contact with infected animals and also consumption of unpasteurized dairy products. Due to the wide incidence of brucellosis in Iran and economical costs in industrial animal husbandry, Vaccination is the best way to prevent this disease. All of the available commercial vaccines against brucellosis are derived from live attenuated strains of Brucella but because of the disadvantage of live attenuated vaccines, protective subunit vaccine against Brucella may be a good candidate for the production of new recombinant vaccines based on Brucella Outer Membrane Protein (OMP) antigens. In the present study, comprehensive bioinformatics analysis has been conducted on prediction software to predict T and B cell epitopes, the secondary and tertiary structures and antigenicity of Omp16 antigen and the validation of used software confirmed by experimental results. Conclusion: The final epitope prediction results have proposed that the three epitopes were predicted for the Omp16 protein with antigenicity ability. We hypothesized that these epitopes likely have the protective capacity to stimulate both the B-cell and T-cell mediated immune responses and so may be effective as an immunogenic candidate for the development of an epitope-based vaccine against brucellosis.
Keywords: outer membrane protein